In Pursuit of Presence or Prominence? The Prospect of Chinese Banks' Global Expansion and Their Benchmarks - Ben, Shenglin (Current Chinese Economic Report Series, 2018)
This book summarizes Chinese banks' achievements in global markets and examines the differences between Chinese and foreign banks. It also explores the future roadmap of internationalization and the risks involved in the process, in order to provide reference resource for Chinese banks. Based on the CBII (Chinese Bank Internationalization Index), which was first released in 2015, the book introduces the Banks' Internationalization Index ("BII") and expands the BII by examining two groups of data, including the number of overseas branches, overseas assets and revenue. In addition it analyzes representative Chinese banks' internationalization, using 16 of the Global Systemically Important Banks (G-SIBs) as benchmarks.